The Cellular Immunoprotection of BALB/C mice vaccinated with Salt-Extractable Brucella abortus S19 antigens and Immunoadjuvant βeta-glucan challenged with Brucella abortus Virulent Strain: Nidhal Raoof Mahdi and Sabrin Ibraheem Mohsin - Mahdi, Nidhal Raoof (The Iraqi Journal of Veterinary Medicine, 2015)
The aim of this study was to evaluate the cellular immune responses of salt-Extractable Brucella abortus S19 antigens with immunoadjuvant soluble βeta-glucan in BALB/C mice later challenged with B. abortus virulent strain. The 0.72mg/ml of SEBA was used according to the results obtained from experiment to determine the macrophages Nitric oxide production and delayed type hypersensitivity test. One hundred BALB/C mice were divided into four groups. G1 were injected i.p with 0.2 ml of saline, G2 were vaccinated S.C with 0.1ml (108 CFU/mouse) of B. abortus S19, G3 were vaccinated i.p. with 0.2 ml of salt-Extractable Brucella abortus S19 antigens and G4 were vaccinated i.p. with 0.2 ml of salt-Extractable Brucella abortus S19 antigens and 0.2ml βeta glucan. At 27 days after immunization the delayed type hypersensitivity test was conducted with the significant (P<0.05) an increase in the foot pad thickness of the G4 as compared to G3, G2 and G1. At day 30 of immunization all remaining mice were i.p. challenged with 0.2ml of 1x104 CFU/ml B. abortus virulent strain. The log10 CFU/spleen count was demonstrated at day 7 and 14 after challenge; G2, G3 and G4 recorded low bacterial count with a significant difference (P<0.01) as compared to the control. In conclusion, this study indicated that immunized mice with salt-Extractable Brucella abortus S19 antigens and β-glucan were effective vaccine, the activated innate immunity was an important key to activate the protective Th1 responses through a significant decrease in the bacterial splenic count after challenge.